Smart Edutainment as a Way of Enhancing Student's Motivation (on the Example of Board Games); Smart Innovation, Systems and Technologies; Vol. 41 : Smart Education and Smart e-Learning - Novikova V. S. Vera Stanislavovna (2015, 2015)
Title screen